Occurrence and Ultrastructure of a Variant (rho) Form of Mycoplasma - Peterson, J. E. (1973)
The ultrastructure of a variant (ρ) form of Mycoplasma is described. The ρ-forms are characterized by dark-ground light microscopy as relatively rigid, unbranched, filamentous organisms with discoidal swellings, and by electron microscopy by the presence of an intracytoplasmic axial fiber extending throughout the length of the cell and associated with a terminal structure of characteristic appearance. In negatively stained preparations the fiber presents a pattern of transverse light and dark major bands, the dark band being divided by a central minor light band. The periodicity of the banding varies from 12.0 to 14.5 nm, and the width of the fiber varies from 40 to 120 nm. The fiber appears to be composed of fibrils aligned parallel to the long axis. The evidence indicates that the fiber contains protein and is devoid of nucleic acid. ρ-Forms were commonly found in Mycoplasma strains derived from goats and occasionally in bovine strains. They may have a wider distribution, as the growth medium was shown to be important both for the expression of the ρ-character and for the selection of the ρ-variant. The functional significance, if any, of the fiber and the terminal structure is unknown.